Amperometric capsaicin biosensor based on covalent immobilization of horseradish peroxidase (HRP) on acrylic microspheres for chilli hotness determination - Rosmawani Mohammad; Musa Ahmad; Lee Yook Heng (Elsevier, 2024)
The evaluation of chilli hotness using amperometric capsaicin biosensor-based enzyme that was immobilized covalently to the surface of modified acrylic microspheres is the first of its kind presented in this work. The immobilization of enzyme covalently to the surface of microspheres via succinimide groups prevented the leaching ofthe enzyme. The enzymatic reaction between horseradish peroxidase-capsaicin in the presence of hydrogen peroxide, which was mediated by vinyl ferrocene, enabled the current measurement at a low potential (0.22V). Besides, the pungency level of the chilli that was proportional to the capsaicin concentration was measured using this method. This biosensor gave a linear response range towards capsaicin from 0.75–24.94 M (R2 = 0.992) with a detection limit at 0.39 M. Moreover, the relative standard deviation (RSD) for reproducibility study was 8.2% (n = 7). Therefore, this biosensor was successfully applied for evaluation of chilli hotness in chilli sample, as well as in comparison with a standard method that employed the HPLC method.